The struggle of democracy against terrorism: lessons from the United States, the United Kingdom, and Israel - Gross, Emanuel (University of Virginia Press, 2006)
What is terrorism? definitions and characteristics -- The laws of war waged between democratic states and terrorist organizations -- Interrogation of terrorists : the boundaries between permitted interrogation and forbidden torture -- Administrative powers of military commanders in the struggle against terrorism -- Administrative detentions and the use of terrorists as bargaining counters -- The right to privacy in times of terrorism -- Use of civilians as human shields -- Thwarting terrorist acts by targeted preventive elimination -- Lessons of the past and challenges for the future.